FISCAL POLICY EFFECTS ON U.S. LABOR MARKET - Kim, Hyeongwoo; Ryu, Deockhyun; Son, Jisoo (Journal of economic development, 2023)
This paper empirically investigates the fiscal policy effects on labor market conditions, employing an array of structural vector autoregressive models for the post-war U.S. data from 1960:I to 2017:II. Fiscal spending shocks increase jobs in the government sector at the cost of private sector jobs, resulting in net losses to the total employment. Private wages increase insignificantly in the short run, while government wages rise significantly and persistently in response to the fiscal shock. Consequently, the wage gap across the two sectors widens in response to the fiscal shock. The wage shock yields significantly positive responses of corporate profits in the long-run as it enhances productivity, which supports wage-led growth models. On the other hand, we report negligible in-sample and out-of-sample predictive contents for private jobs and wages from corporate profits, meaning that there's virtually no evidence of the trickle-down effect, which is essential for profit-led growth models.